Dinero electrónico y banca móvil: economía para el desarrollo en el Ecuador - Sánchez Puga, Adrián Fernando (2025)
The study examines the growing adoption of electronic banking and the types of services it offers to customers. Digital transformation has changed and revolutionized the financial sector, especially with electronic money and mobile banking. This essay analyses the effects of innovations on operational efficiency, financial inclusion, and associated risks. Mobile banking and electronic money have become an important tool for the financial management of the productive sector, allowing users to make bank transactions, check balances and control accounts from their mobile devices. This study highlights how the use of mobile banking and electronic money has increased significantly in Ecuador in recent years, driven by the use and handling of smartphones with internet access, the need to be included in the increasingly evolved electronic environment and the accessibility of electronic services that have facilitated greater financial inclusion, especially in regions where financial institutions are located in areas where financial institutions are out of their reach. Both types of technological tools have improved the management of banking operations, reducing operating costs and increasing the speed of transactions. In addition, they play a crucial role in inclusion by providing access to financial services to people in Ecuador who do not have an adequate financial culture.